2012
DOI: 10.1093/cvr/cvs136
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein receptor-related protein 1 mediates hypoxia-induced very low density lipoprotein-cholesteryl ester uptake and accumulation in cardiomyocytes

Abstract: Our results demonstrate that hypoxia increases LRP1 expression through HIF-1α and that LRP1 overexpression mediates hypoxia-induced VLDL-CE uptake and accumulation in cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 39 publications
8
72
1
Order By: Relevance
“…We previously showed that hypoxia-induced LRP1 overexpression is mediated by HIF-1α in hVSMCs and HL-1 cells. 16,17 HIF-1α expression depends on intracellular calcium concentrations that rapidly and persistently increase in response to hypoxia. 31,32 Hypoxia-induced Pyk2 phosphorylation has been associated to a hypoxia-induced increase in calcium cytosolic levels.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that hypoxia-induced LRP1 overexpression is mediated by HIF-1α in hVSMCs and HL-1 cells. 16,17 HIF-1α expression depends on intracellular calcium concentrations that rapidly and persistently increase in response to hypoxia. 31,32 Hypoxia-induced Pyk2 phosphorylation has been associated to a hypoxia-induced increase in calcium cytosolic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Human VSMC were preexposed to agLDL (100 μg/mL) for 18 hours before addition of cycloheximide (Sigma, 100 μmol/L). Cells were harvested at various time points after cycloheximide treatment (6,12,24, and 32 hours) and collected in lysis buffer, and protein processed for Western blot analysis. LRP1 protein stability was assessed as the proportion of the initial protein remaining after cycloheximide treatment.…”
Section: Measurement Of Lrp1 Stability After Exposure To Agldlmentioning
confidence: 99%
“…Our group reported that LRP1 is upregulated at transcriptional level by hypercholesterolemia through sterol regulatory element-binding proteins (SREBP) downregulation in human VSMC, [8][9][10] and by hypoxia through hypoxia-inducible factor 1α upregulation in human VSMC 11 and cardiomyocytes. 12,13 Other groups have reported that insulin promotes the presence of LRP1 in the plasma membrane without influencing mRNA expression levels. 14,15 LRP1 cellular turnover is regulated by the ubiquitinproteasome system, 16 an important mechanism for targeting membrane proteins to destruction, and therefore key in the modulation of protein levels.…”
mentioning
confidence: 99%
“…Here, we also show that one of the mechanisms leading to higher intracellular TG accumulation under hypoxia is the increased uptake of LDL(+) and LDL(−) by cardiomyocytes exposed to hypoxic conditions. We have previously reported that the classical LDL receptor recognizes LDL(−) with a lower affinity than native LDL , and that this receptor is downregulated in hypoxic cardiomyocytes (Cal et al, 2012a). These observations suggest that alternative receptors whose expression is upregulated by hypoxia may be involved.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, LRP1 internalizes aggregated LDL (Llorente-Cortes et al, 2000). Moreover, hypoxia upregulates the expression of CD36 (Mwaikambo et al, 2009), LOX-1 (Crucet et al, 2013) and LRP1 (Castellano et al, 2011a, Cal et al, 2012a. Thus, one or several of these receptors could be involved in the increased uptake of LDL(−) by cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%